INTEGRASI KURIKULUM IPA DAN MATEMATIKA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN ABAD 21 - Amaza Ilmil Mufidah; Anzilna Qotrun Nada; Indah Wahyuni; Umi Farihah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of developing students’ critical thinking skills in 21st-century learning through the integration of Science and Mathematics curricula in elementary schools. Learning processes that are still conducted separately often cause students to have difficulty understanding the relationship between concepts and solving contextual problems effectively. This study aims to describe the implementation of the integration of Science and Mathematics curricula, analyze the improvement of students’ critical thinking skills, and identify the supporting and inhibiting factors in the implementation of integrated learning in elementary schools. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of principals, teachers, and students involved in the learning process. Data analysis used the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The results showed that the integration of Science and Mathematics curricula was able to create more active, contextual, and meaningful learning experiences. Students became more active in discussions, problem analysis, data processing, and drawing conclusions based on observations. Integrated learning was also proven to improve students’ critical thinking skills through experiments, problem-solving activities, and group discussions. Supporting factors in the implementation of integrated learning included teacher creativity, school support, and students’ enthusiasm, while the inhibiting factors included limited learning time and teachers’ difficulties in designing integrated learning tools. Therefore, the integration of Science and Mathematics curricula can be an effective learning strategy in improving students’ critical thinking skills in 21st-century learning at the elementary school level.